Anatomia óssea e muscular da cintura peitoral, estilopódio e zeugopódio do Caiman latirostris (DAUDIN, 1802) (Crocodylia: Alligatoridae) - Romão, Mariluce Ferreira (2010)
CHAPTER II: The development of the skeleton can be better understood through new discoveries, using as reference tissue that is in a dynamic process of formation and resorption. This study used a young adult male specimen of C. latirostris, 1.50m in length, belonging to the collection of the Wild Animal Research Laboratory of the Federal University of Uberlândia, fixed in 10% formol. The specimen s skin, viscera and pectoral girdle, stylopodium and zeugopodium bone muscles were removed, and the bones were identified, recorded in photographs taken with a digital camera, and described. The findings demonstrate that the characteristics of the skeletal anatomy of the pectoral girdle, stylopodium and zeugopodium of C. latirostris resemble those of its ancestors and extend to the other crocodilians, since they exhibit inter- and intraspecific behavioral similarities. CHAPTER III: The parameters of muscle origin and insertion points in the pectoral girdle, estilopodium and zeugopodium of Caiman latirostris were identified using a basic anatomical, kinesiological and biomechanical approach. This identification was made using a young adult male specimen of C. latirostris, 1.50 m in length, belonging to the collection of the Wild Animal Research Laboratory of the Federal University of Uberlândia. The specimen was dissected and the muscles of the pectoral girdle, stylopodium and zeugopodium were separated individually and identified. This required the removal of the limbs to facilitate the observation of the origins and insertion points of the muscles. In this study, whose nature was observational, isometric postures intercalated with rotary movements were found, as well as a large cross-sectional area in most of the extensor and stabilizer muscles, giving them greater strength and denoting functional and organizational inferences. Muscle activity and structural shapes may serve as indicators for basic anatomical, kinesiological and biomechanical analyses, underpinned by well known concepts widely accepted by the scientific community, as indicated in the references of this research. Based on the findings, which were duly documented, it was possible to recognize and predefine the behavior of the species under investigation, correlating the duration, direction and dimension of the levels of activity. It is believed that muscle activity is associated with the species needs and phylogeny.